A multilevel research perspective on cancer care delivery: the example of follow-up to an abnormal mammogram - Taplin, Stephen H. (2012)
In 1999, researchers and policy makers recognized the challenge of creating an integrated patient-centered cancer care process across the many types of care from risk assessment through end of life. More than a decade later, there has been limited progress towards that goal even though the standard reductionist approach to health services and medical research has resulted in major advances in tests, procedures, and individualized patient approaches to care. In this commentary, we propose that considering an entire care process within its multilevel context may increase progress towards an integrated experience and improvements in the quality of care. As an illustrative case, we describe the multilevel context of care delivery for the process of follow-up to an abnormal screening mammogram. By taking a multilevel perspective on this process, we identify a rich set of options for intervening and improving follow-up to abnormalities and therefore outcomes of screening. We propose that taking this multilevel perspective when designing interventions may improve the quality of cancer care in an effective and sustainable way.